Assessment of Water Quality Index in Some Selected Local Government Area of Taraba State - Precious, Omale Owoicho; Ruth, Adelagun A.O; John, Oko Odiba; AM, Abakpa; Ngana, Obinna C.; Timothy, Japhet (African Journal of Sciences and Traditional Medicine, 2024)
Using the water quality index (WQI) technique, this study was conducted to evaluate the water quality for drinking purposes in a few chosen local governments in Taraba State. The goal of WQI assessment is to combine various physicochemical properties of water into a single figure that both specialists and laypeople can understand. Twelve important physico-chemical parameters used in the aggregation of the WQI were: Sulphate, Phosphate, Magnesium, Turbidity, pH, Electrical conductivity (EC), Total dissolved solids (TDS), Nitrate (NO 3), calcium, hardness, fluoride and chloride composition. The water samples analyzed were obtained from three different sources in the selected areas. The comparison of the physicochemical parameters' results with the standards suggested by WHO and NSDWQ revealed that, with the exception of fluoride in some samples, they were within the limits defined by these organisations. The results of the WQI computation revealed that the index values ranged from 50.0, which is "poor" and unfit for consumption, to 42.20, which falls within the "good" water quality category and is suitable for human consumption and other domestic uses.